2014
DOI: 10.1007/s12639-014-0488-5
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and morphological studies on natural Cysticercus fasciolaris infection in liver of Wistar rats

Abstract: Descriptive morphology of multifocal hepatic cysts found in eight of forty five (17.78 %) Wistar rats sacrificed during pharmacological studies related to herbal formulations was studied. The creamish to white cysts were of varying sizes, ranging from 3-8 mm in diameter. Morphological studies of these cysts depicted the presence of metacestodes of Taenia taeniaeformis i.e. Cysticercus fasciolaris inside them. The scolex of metacestode revealed four suckers and rostellum armed with two distinct rows of characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 9 publications
4
15
0
Order By: Relevance
“…Similar studies have shown two layers of connective tissue around the larva [19]. Also, aggregation of lymphocytes, plasmocytes, and eosinophils in the outer layer of cyst shows the acute nature of infection [15]. Previously, infiltration of mononuclear cells including lymphocytes, 2017 Vol.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Similar studies have shown two layers of connective tissue around the larva [19]. Also, aggregation of lymphocytes, plasmocytes, and eosinophils in the outer layer of cyst shows the acute nature of infection [15]. Previously, infiltration of mononuclear cells including lymphocytes, 2017 Vol.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the infected livers had multiple cysts, which may reflect the number of ingested eggs [18]. Other studies have shown the variation in the size of the cysts that might be due to infection at different time intervals [15]. In this study, histopathology of the liver demonstrated a two layer cyst around the C. fasciolaris larva, which might be a defense mechanism to limit the growth of the larva [19].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations